The role of offspring in mitigating extreme stress in lactating female mice - Homer, Jennifer (My University, 2009)
Mothers of many species find great comfort in their offspring, which in turn has been found to alleviate mild stress in the mother. In the face of a life-threatening event, however, do offspring still act as effective stress reducers? Using mice as test subjects, I investigated how variable exposure time to pups affects a mother's anxiety levels after being subjected to a major stressor. It was found that exposure to pups alleviates fear and anxiety in lactating females after an extreme stressor. Additionally, the mothers who recovered without their pups in the original home cage, with only the smell of their pups, experienced the least amount of stress reduction and the highest anxiety levels compared to the other treatment groups. We believe this absence of pups in the home cage created a "double stressor", which added to the stress created by the major stressor, ultimately leading to a greater increase in anxiety.
18 p.
Keywords: Neuroscience; Zoology; Biology